Pengaruh Model Multiple Inttelligence Terhadap Hasil Belajar Siswa Pada Materi Sistem Koloid kelas XI IPA SMA Negeri 2 Tondano - novinus rerung; Marlina Karundeng; jenny kumajas (Oxygenius: Journal Of Chemistry Education, 2022)
A B S T R A C TThis study aims to determine the effect of the Multiple Intelligence model on chemistry learning outcomes student in colloidal system material. This research was conducted from May to June for the 2021/2022 school year, students of class XI IPA at SMA Negeri 2 Tondano. The sampling technique was carried out using random sampling. The samples used in this study were 22 students of class XI IPA 1 as the experimental class and 22 students in class XI IPA 2 as the control class. The research design used was the Pretest-Postest Control Group Design. Research data on learning outcomes were measured after treatment in the experimental and control classes, then data analysis was carried out using Analysis of Covariance (ANCOVA) to test the formulation of hypotheses with the testing criteria, namely reject Ho if Fcount>Ftable. The research results obtained for learning outcomes are Fcount>Ftable, at the real level α=0.05 and db=42, namely Fcount= 36.378>Ftable=1.671, so Ho is rejected and H1 is accepted. Based on the data analysis, it can be concluded that the use of the Multiple Intelligence model has an effect on chemistry learning outcomes student’s.